Investigating The Impact of The 3cm Model on Enhancing Students’ Critical Thinking Skills - Nur Janah; Ifa Fauziah; Deny Hadi Siswanto (Universitas Ahmad Dahlan, 2026)
This research aims to assess the effect of the Cool, Critical, Creative, and Meaningful (3CM) learning model in improving students' critical thinking skills on the topic of matrices. A quantitative approach was used, employing a pre-experimental design with a one-group pretest-posttest format. The study involved 30 11th-grade science students from SMA Muhammadiyah Mlati. The instruments for this research included a critical thinking skills test based on the indicators of Focus, Reason, Inference, Situation, Clarity, and Overview, as well as a student perception questionnaire regarding the 3CM learning model. The validity and reliability tests showed that all instruments were valid and reliable. Tests for normality and linearity confirmed that the data were normally distributed and exhibited a significant linear relationship. Regression analysis demonstrated a positive and significant correlation between the 3CM model and students’ critical thinking skills (sig. = 0.003 < 0.05), with the model explaining 27.7% of the variance. The average pretest score of 61.56 increased to 85.80 in the posttest, with the greatest improvement observed in the Situation indicator. These findings indicate that the 3CM model is effective in enhancing students' critical thinking skills and contributes to the development of innovative teaching strategies in mathematics education.